An Investigation of Interpersonal Ties in Interorganizational Exchanges in Emerging Markets: A Boundary-Spanning Perspective. (September 2016) - Huang, Ying; Luo, Yadong; Liu, Yi; Yang, Qian
This study examines personal ties between boundary-spanning personnel in interorganizational exchanges in emerging markets. Drawing on social embeddedness theory and boundary spanning theory, we propose that strong ties between boundary spanners may benefit exchange parties in their interorganizational relationships through two heightened boundary-spanning behaviors—information processing and external representation. The results from 225 manufacturer–distributor dyads in China indicate that interpersonal ties at the higher levels (between top executives) and at the lower levels (between salespersons and individual buyers) are both positively associated with relationship quality of the buyer–supplier relationship through dyadic boundary-spanning behaviors. Between two levels of interpersonal ties, ties at the lower levels exhibit a stronger association with relationship quality than do ties at the higher levels. Furthermore, the positive effects of interpersonal ties on conflict resolution and cooperation are amplified when both levels of ties are strong in the focal relationship.